Crystal structure and local order of nanocrystalline zirconia-based solid solutions - Fabregas, Ismael Oscar (2008)
Crystal and local structures long- and short-range order, respectively of four nanocrystalline zirconia-based solid solutions—ZrO2-6 and 16 mol % CaO and ZrO2-2.8 and 12 mol % Y2O3—synthesized by a pH-controlled nitrate-glycine gel-combustion process were studied. These materials were characterized by synchrotron X-ray diffraction XRD and extended X-ray absorption fine structure EXAFS spectroscopy. Our XRD results indicate that the solid solution with low CaO and Y2O3 contents 6 and 2.8 mol %, respectively exhibit a tetragonal crystallographic lattice, and those with higher CaO and Y2O3 contents 16 and 12 mol %, respectively have a cubic lattice. Moreover, our EXAFS study demonstrates that the tetragonal-to-cubic phase transitions, for increasing CaO and Y2O3 contents, are both related to variations in the local symmetry of the Zr–O first neighbor coordination spherelong- and short-range order, respectively of four nanocrystalline zirconia-based solid solutions—ZrO2-6 and 16 mol % CaO and ZrO2-2.8 and 12 mol % Y2O3—synthesized by a pH-controlled nitrate-glycine gel-combustion process were studied. These materials were characterized by synchrotron X-ray diffraction XRD and extended X-ray absorption fine structure EXAFS spectroscopy. Our XRD results indicate that the solid solution with low CaO and Y2O3 contents 6 and 2.8 mol %, respectively exhibit a tetragonal crystallographic lattice, and those with higher CaO and Y2O3 contents 16 and 12 mol %, respectively have a cubic lattice. Moreover, our EXAFS study demonstrates that the tetragonal-to-cubic phase transitions, for increasing CaO and Y2O3 contents, are both related to variations in the local symmetry of the Zr–O first neighbor coordination sphere2-6 and 16 mol % CaO and ZrO2-2.8 and 12 mol % Y2O3—synthesized by a pH-controlled nitrate-glycine gel-combustion process were studied. These materials were characterized by synchrotron X-ray diffraction XRD and extended X-ray absorption fine structure EXAFS spectroscopy. Our XRD results indicate that the solid solution with low CaO and Y2O3 contents 6 and 2.8 mol %, respectively exhibit a tetragonal crystallographic lattice, and those with higher CaO and Y2O3 contents 16 and 12 mol %, respectively have a cubic lattice. Moreover, our EXAFS study demonstrates that the tetragonal-to-cubic phase transitions, for increasing CaO and Y2O3 contents, are both related to variations in the local symmetry of the Zr–O first neighbor coordination sphere2O3—synthesized by a pH-controlled nitrate-glycine gel-combustion process were studied. These materials were characterized by synchrotron X-ray diffraction XRD and extended X-ray absorption fine structure EXAFS spectroscopy. Our XRD results indicate that the solid solution with low CaO and Y2O3 contents 6 and 2.8 mol %, respectively exhibit a tetragonal crystallographic lattice, and those with higher CaO and Y2O3 contents 16 and 12 mol %, respectively have a cubic lattice. Moreover, our EXAFS study demonstrates that the tetragonal-to-cubic phase transitions, for increasing CaO and Y2O3 contents, are both related to variations in the local symmetry of the Zr–O first neighbor coordination sphereXRD and extended X-ray absorption fine structure EXAFS spectroscopy. Our XRD results indicate that the solid solution with low CaO and Y2O3 contents 6 and 2.8 mol %, respectively exhibit a tetragonal crystallographic lattice, and those with higher CaO and Y2O3 contents 16 and 12 mol %, respectively have a cubic lattice. Moreover, our EXAFS study demonstrates that the tetragonal-to-cubic phase transitions, for increasing CaO and Y2O3 contents, are both related to variations in the local symmetry of the Zr–O first neighbor coordination sphereEXAFS spectroscopy. Our XRD results indicate that the solid solution with low CaO and Y2O3 contents 6 and 2.8 mol %, respectively exhibit a tetragonal crystallographic lattice, and those with higher CaO and Y2O3 contents 16 and 12 mol %, respectively have a cubic lattice. Moreover, our EXAFS study demonstrates that the tetragonal-to-cubic phase transitions, for increasing CaO and Y2O3 contents, are both related to variations in the local symmetry of the Zr–O first neighbor coordination sphere2O3 contents 6 and 2.8 mol %, respectively exhibit a tetragonal crystallographic lattice, and those with higher CaO and Y2O3 contents 16 and 12 mol %, respectively have a cubic lattice. Moreover, our EXAFS study demonstrates that the tetragonal-to-cubic phase transitions, for increasing CaO and Y2O3 contents, are both related to variations in the local symmetry of the Zr–O first neighbor coordination sphere2O3 contents 16 and 12 mol %, respectively have a cubic lattice. Moreover, our EXAFS study demonstrates that the tetragonal-to-cubic phase transitions, for increasing CaO and Y2O3 contents, are both related to variations in the local symmetry of the Zr–O first neighbor coordination sphere have a cubic lattice. Moreover, our EXAFS study demonstrates that the tetragonal-to-cubic phase transitions, for increasing CaO and Y2O3 contents, are both related to variations in the local symmetry of the Zr–O first neighbor coordination sphere2O3 contents, are both related to variations in the local symmetry of the Zr–O first neighbor coordination sphere.